Living Close to the Edge: Embodied Dimensions of Distress During Emerging Adulthood. (20th May 2014) - Wiklund, Maria; Öhman, Ann; Bengs, Carita; Malmgren-Olsson, Eva-Britt
Although self-reported stress-related problems are common among Swedish adolescent girls and young women, few qualitative studies have been carried out of young people's own understandings and descriptions of their lived embodied experiences of stress-related illness. The aim of the present study, therefore, was to explore and analyze the lived embodied experiences of stress among adolescent girls and young women who had sought help at a youth health center. Interviews with 40 girls and young women aged 16 to 25 were analyzed with qualitative content analysis. "Living close to the edge" was interpreted as the common theme running through all of the interviews and representing the participants' sometimes unbearable situations. The theme contains embodied dimensions of physical, emotional, cognitive, social, and existential distress, as well as dimensions of distrust and disempowerment. The findings highlight the importance of addressing these dimensions in youth health interventions, and the importance of contextualizing young women's distress is emphasized. These young women's experiences of stress and illness were multifaceted, which place high demands on health facilities and intervention programs. It is important to integrate context- and gender-sensitive models and approaches in youth health as well as in primary care settings.